Changing Tides: A Review of Cape Cod's Suburbanization and its Suitability for MBTA Commuter Rail Service - Higgins, Patrick. (Tufts University. Tisch Library., 2021)
Thesis (M.A.)--Tufts University, 2021.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Jon Witten.; Committee: Mark Chase.; Keywords: Transportation, Environmental economics, and Statistics.